Pharmacotherapy for Erectile Dysfunction: Recommendations From the Fourth International Consultation for Sexual Medicine (ICSM 2015). Issue 4 (1st April 2016) - Hatzimouratidis, Konstantinos; Salonia, Andrea; Adaikan, Ganesan; Buvat, Jacques; Carrier, Serge; El-Meliegy, Amr; McCullough, Andrew; Torres, Luiz Otavio; Khera, Mohit
ABSTRACT: Introduction: Treatment of erectile dysfunction is based on pharmacotherapy for most patients. Aim: To review the current data on pharmacotherapy for erectile dysfunction based on efficacy, psychosocial outcomes, and safety outcomes. Methods: A review of the literature was undertaken by the committee members. All related articles were critically analyzed and discussed. Main Outcome Measures: Levels of evidence (LEs) and grades of recommendations (GRs) are provided based on a thorough analysis of the literature and committee consensus. Results: Ten recommendations are provided. (i) Phosphodiesterase type 5 (PDE5) inhibitors are effective, safe, and well-tolerated therapies for the treatment of men with erectile dysfunction (LE = 1, GR = A). (ii) There are no significant differences in efficacy, safety, and tolerability among PDE5 inhibitors (LE = 1, GR = A). (iii) PDE5 inhibitors are first-line therapy for most men with erectile dysfunction who do not have a specific contraindication to their use (LE = 3, GR = C). (iv) Intracavernosal injection therapy with alprostadil is an effective and well-tolerated treatment for men with erectile dysfunction (LE = 1, GR = A). (v) Intracavernosal injection therapy with alprostadil should be offered to patients as second-line therapy for erectile dysfunction (LE = 3, GR = C). (vi) Intraurethral and topical alprostadil are effective and well-tolerated treatments for men with erectile dysfunction (LE = 1, GR = A). (vii) Intraurethral and topical alprostadil should be considered second-line therapy for erectile dysfunction if available (LE = 3, GR = C). (viii) Dose titration of PDE5 inhibitors to the maximum tolerated dose is strongly recommended because it increases efficacy and satisfaction from treatment (LE = 2, GR = A). (ix) Treatment selection and follow-up should address the psychosocial profile and the needs and expectations of a patient for his sexual life. Shared decision making with the patient (and his partner) is strongly recommended (LE = 2, GR = A). (x) Counterfeit medicines are potentially dangerous. It is strongly recommended that physicians educate their patients to avoid taking any medication from unauthorized sources (LE = 2, GR = A). The first seven recommendations are the same as those from the Third International Consultation for Sexual Medicine and the last three are new recommendations. Conclusion: PDE5 inhibitors remain a first-line treatment option because of their excellent efficacy and safety profile. This class of drugs is continually developed with new molecules and new formulations. Intracavernosal injections continue to be an established treatment modality, and intraurethral and topical alprostadil provide an alternative, less invasive treatment option.